A Near Chromosome Assembly of the Dromedary Camel Genome - Ruvinskiy, Daniil; Larkin, Denis M.; Farré, Marta (Frontiers in Genetics, 2019)
The dromedary camel is an economically and socially important species of livestock in many parts of the world, being used for transport and the production of milk and meat. Much like cattle and horses, the camel may be found in industrial farming conditions as well as used in sporting. Camel racing is a multi-million dollar industry, with some specimens being valued at upward of 9.5 million USD. Despite its apparent value to humans, the dromedary camel is a neglected species in genomics. While cattle and other domesticated species have had much attention in terms of genome assembly, the camel has only been assembled to scaffold level, which does not give a clear indication of the order or chromosomal location of sequenced fragments. In this study, the Reference Assistant Chromosome Assembly (RACA) algorithm was implemented to use read-pair information of camel scaffolds, aligned with the cattle and human genomes in order to organize and orient these scaffolds in a near-chromosome level assembly. This method generated 72 large size fragments (N50 54.36 Mb). These predicted chromosome fragments (PCFs) were then compared with comparative maps of camel and cytogenetic map of alpaca chromosomes, allowing us to further upgrade the assembly. This dromedary camel assembly will be an invaluable tool to verify future camel assemblies generated with chromatin conformation or/and long read technologies. This study provides the first near-chromosome assembly of the dromedary camel, thus adding this economically important species to a growing pool of knowledge regarding the genome structure of domesticated livestock.